SPICE Mutator Model for Transforming Memristor into Meminductor - Hui Wang; Xin Wang; Chuandong Li; Ling Chen (Abstract and Applied Analysis)
The memristor (resistor with memory), as the fourth fundamental circuit element, is a nonvolatile nanoelectronic device and holds great promise for VLSI applications. It was suggested that the meminductor (ML, inductor with memory) circuit can be built by memristor emulators. This paper further addresses the transformation mechanism in terms of constitutive relation from the memristor to the meminductor and then designs an MR-ML mutator to achieve MR-ML transformation. We also present the mutator’s SPICE model and analyze the simulation results.